Electrode material, preparation method thereof and three-electrode sodium ion battery
By setting high rough conductive layers on the conductive substrate of the sodium ion battery reference electrode, the problem of the existing sodium ginseng -plated sodium -plated amount is solved, and the stability of the sodium plating layer and the service life of the battery are improved. Essence
Patent Information
- Application Number
- CN202411511018.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The existing sodium-plated reference electrode has a small amount of sodium plating, resulting in poor stability and life.
The conductive layer with high roughness is set on the conductive substrate. The surface roughness of the conductive layer is 0.3 μm-3 μm. In the process of electrochemical deposition sodium metal, the contact area of the electrode material and sodium metal metal is increased to increase the amount of sodium plating. And enhance the spatial limit capacity of powder -shaped sodium metal on the surface of the electrode material.
It significantly improves the stability of the sodium plating layer and the service life of the sodium ion battery reference electrode, and at the same time improves the amount of sodium plating, and enhances the accuracy of electrochemical performance detection.
Smart Images

Figure CN119381460A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion battery analysis and testing, and specifically to an electrode material and a preparation method thereof and a three-electrode sodium ion battery. Background Art
[0002] The three-electrode technology of lithium-ion batteries has developed into a mature method for battery development and failure analysis, and plays an important role in lithium precipitation window detection, full electrical impedance decomposition, and research on positive and negative electrode charge and discharge behavior. In recent years, the industrialization of sodium-ion batteries has developed rapidly, and the demand for all-round electrochemical performance testing of sodium-ion batteries has become increasingly prominent. Therefore, it is also particularly important to develop a sodium-ion battery three-electrode system with long life and high precision.
[0003] In the prior art, the metal wire sodium plating method is often used to prepare the reference electrode for the three-electrode sodium ion battery. This method is to etch the metal wire with concentrated acid and then place it in the battery cell, and use an electrochemical deposition process to deposit a layer of sodium metal on the surface of the metal wire, thereby obtaining a sodium-plated reference electrode with a constant potential. The above method is a direct application of the metal wire lithium-plated reference electrode technology in sodium ion batteries, but practice shows that the sodium-plated reference electrode prepared in this way has a small amount of sodium plating, resulting in the stability and life of the sodium-plated reference electrode being far inferior to that of the lithium-plated reference electrode. Summary of the invention
[0004] In view of this, the present application provides an electrode material for a sodium ion battery reference electrode to solve the problem of low sodium plating amount in existing sodium-plated reference electrodes.
[0005] The present application also provides a method for preparing a three-electrode sodium ion battery to solve the problems of small amount of sodium plating, long sodium plating time, and poor uniformity and density of the sodium plating layer in the existing process.
[0006] According to an embodiment of the present application, in a first aspect, an electrode material is provided for a reference electrode of a sodium ion battery, wherein the electrode material comprises a conductive substrate and a conductive layer coated on one end of the conductive substrate, wherein the surface roughness of the conductive layer is 0.3 μm-3 μm.
[0007] In some optional embodiments, the surface roughness of the conductive layer is 1.1 μm-2.3 μm.
[0008] In some optional embodiments, the thickness of the conductive layer is 1 μm-20 μm.
[0009] In some optional embodiments, the thickness of the conductive layer is 10 μm-17 μm.
[0010] In some optional embodiments, the conductive layer includes 80%-98% of carbon material and 2%-20% of aqueous binder.
[0011] In some optional embodiments, the specific surface area of the carbon material is 200 m 2 / g-1000m 2 / g.
[0012] In some optional embodiments, the carbon material includes at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene.
[0013] In some optional embodiments, the aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, and polyacrylic acid.
[0014] In some optional embodiments, the height of the conductive layer on the conductive substrate accounts for 0.5%-5% of the length of the conductive substrate.
[0015] In some optional embodiments, the conductive substrate has a diameter of 10 μm-200 μm.
[0016] In some optional embodiments, the conductive substrate includes any one of metal wire, enameled metal wire, and carbon fiber product.
[0017] According to an embodiment of the present application, in a second aspect, a method for preparing the electrode material according to the first aspect is provided, comprising the following steps:
[0018] S1. Evenly mix the carbon material, aqueous binder and deionized water to prepare a conductive layer slurry with a solid content of 1% to 20%;
[0019] S2, wetting one end of the pretreated conductive substrate with deionized water, and then immersing it in the conductive layer slurry and keeping it for the first time, taking it out, and drying it.
[0020] In some optional implementations, the first time is 5s-30s.
[0021] In some optional embodiments, the pretreatment step includes: when the conductive substrate is a metal wire or an enameled metal wire, placing the two ends of the conductive substrate in dilute acid to remove oxides or enameling layers; or, when the conductive substrate is a carbon fiber product, cleaning it with deionized water and / or ethanol.
[0022] According to an embodiment of the present application, in a third aspect, a method for preparing a three-electrode sodium ion battery is provided, comprising the following steps:
[0023] S1. Covering the surface of the conductive layer of the electrode material with a separator and placing it in the middle of the battery core; the electrode material is the electrode material described in the first aspect or the electrode material prepared by the preparation method described in the second aspect;
[0024] S2. After the battery cell is packaged, baked, injected, formed, and divided in sequence, a sodium plating layer is deposited on the surface of the conductive layer using a step current sodium plating process; the step current sodium plating process includes: charging with a current of 1mA-5mA for 1min-5min, a current of 200μA-1000μA for 5min-10min, a current of 50μA-200μA for 10min-30min, and a current of 3μA-50μA for 30min-240min.
[0025] In some optional embodiments, the mass ratio of the sodium plating layer to the electrode material is 1:100-1:40.
[0026] According to an embodiment of the present application, in a fourth aspect, a three-electrode sodium ion battery is also provided, which is prepared using the preparation method described in the third aspect.
[0027] The technical solution of this application has the following advantages:
[0028] The electrode material for the reference electrode of a sodium ion battery provided in the present application comprises a conductive substrate and a conductive layer coated on one end of the conductive substrate, wherein the surface roughness of the conductive layer is 0.3 μm-3 μm. By providing a high-roughness conductive layer on the conductive substrate, during the electrochemical deposition of sodium metal, on the one hand, the contact area between the electrode material and the sodium metal can be increased, and the amount of sodium plating can be increased; on the other hand, the spatial limiting ability of the powdered sodium metal on the surface of the electrode material can be enhanced, so as to avoid the failure of the sodium-plated reference electrode due to the shedding of the sodium metal, improve the stability of the sodium-plated layer, and ensure the service life of the sodium-plated reference electrode.
[0029] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 It is a cross-sectional view of a cell of a three-electrode sodium-ion battery of the present application.
[0032] Figure 2 It is a schematic diagram of the position of the reference electrode in the three-electrode sodium ion battery of the present application.
[0033] Figure 3is the three-electrode potential diagram of Example 1.
[0034] Figure 4 This is the three-electrode potential diagram of Comparative Example 1.
[0035] The reference numerals are described as follows:
[0036] 1. Positive electrode ear; 2. Negative electrode ear; 3. Aluminum-plastic film shell; 4. Reference electrode ear; 5. Effective part of reference electrode; 6. Enameled metal wire; 7. Positive electrode sheet; 8. Negative electrode sheet; 9. Diaphragm. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0039] The applicant has found that the main reason for the low sodium content in the sodium-plated reference electrode prepared by the prior art is that the long strip-shaped lithium crystals can form a dense lithium metal layer on the surface of the metal wire, but the sodium metal is petal-shaped, and it accumulates on the surface of the metal wire in the form of fluffy powder, resulting in a small amount of sodium plating per unit volume, and also makes the contact area between the sodium metal layer and the electrolyte larger, which is very easy to cause the sodium metal to detach or deactivate. For this reason, the related art proposes to use acid-etched carbon fiber products as reference substrates, and use the large number of irregular surface layers produced by etching to increase the deposition area and adhesion of sodium metal, thereby increasing the amount of sodium plating while improving the density of the sodium plating layer. However, this technology uses concentrated acid as an etchant, which has the defects of high difficulty in operation, long etching time, and large waste acid pollution, and the cost of carbon fiber products is significantly higher than that of metal wire, further increasing the preparation cost of three-electrode batteries.
[0040] In order to solve the above-mentioned problems existing in the related art, according to the first aspect of the present application, an electrode material for a reference electrode of a sodium ion battery is provided, the electrode material comprising a conductive substrate and a conductive layer coated on one end of the conductive substrate, the surface roughness of the conductive layer is 0.3 μm-3 μm, for example, it can be 0.3 μm, 0.7 μm, 1.1 μm, 1.5 μm, 1.8 μm, 2.3 μm, 2.6 μm, 3 μm, etc. or within the range formed by any two of the above values. By providing a high-roughness conductive layer on the conductive substrate, in the process of electrochemical deposition of sodium metal, on the one hand, the contact area between the electrode material and the sodium metal can be increased, and the amount of sodium plating can be increased, and on the other hand, the spatial limiting ability of the powdered sodium metal on the surface of the electrode material can be enhanced, so as to avoid the failure of the sodium-plated reference electrode due to the shedding of the sodium metal, improve the stability of the sodium-plated layer, and ensure the service life of the sodium-plated reference electrode.
[0041] It should be noted that the thickness of the conductive layer in the electrode material is 1 μm-20 μm, which will not affect the performance of the battery cell and can provide a suitable high-roughness surface for the deposition of sodium metal. As an example, the thickness of the conductive layer can be 1 μm, 2.5 μm, 5 μm, 7.5 μm, 10 μm, 12.5 μm, 15 μm, 17 μm, 20 μm, etc. or within the range of any two of the above values.
[0042] The applicant has found that the carbon material has a low dispersibility in deionized water, so a high-roughness conductive layer can be obtained by constructing a low-dispersion system of carbon material / aqueous binder / deionized water. Since the deionized water needs to be volatilized during the formation of the conductive layer, in some embodiments, the conductive layer includes 80%-98% of the carbon material and 2%-20% of the aqueous binder. As an example, the mass ratio of the carbon material to the aqueous binder in the conductive layer is 80:20, 85:15, 90:10, 95:5, 98:2, etc. or is within the range of any two of the above values. High conductivity can be ensured within the above ratio range, thereby giving the conductive layer excellent electron / ion transmission capabilities. If the content of the aqueous binder is too high, the internal resistance increases and the battery polarization is aggravated. If the content of the aqueous binder is too low, it is difficult to form a conductive layer with good adhesion. As an example, the aqueous binder includes at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), polyacrylonitrile (PAN), and polyacrylic acid (PAA).
[0043] The applicant has found that the conductive layer formed by using a carbon material with a high specific surface area can further increase the deposition area of sodium metal and ensure that a uniform and dense sodium metal deposition is formed in the thickness direction of the coating. In some embodiments, the specific surface area of the carbon material is 200 m 2 / g-1000m 2 / g, as an example, it can be 200m 2 / g, 350m 2 / g、500m 2 / g, 750m 2 / g、1000m 2 / g, or within the range formed by any two of the above values, the carbon material includes at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene.
[0044] For ease of use, one end of the reference electrode is the effective part of the electrode, and a sodium-plated layer is deposited thereon. When in use, the effective part of the electrode is placed in the battery cell, and the other end of the reference electrode needs to be led out of the battery cell to form an external reference electrode tab. Therefore, in the electrode material of the present application, the conductive layer only needs to be arranged at the effective part of the electrode, that is, the height of the conductive layer on the conductive substrate accounts for 0.5%-5% of the length of the conductive substrate. As an example, the ratio can be 0.5%, 1%, 2%, 3%, 4%, 5%, etc. or within the range of any two of the above values, and the length of the conductive substrate is adapted to the size of the battery cell.
[0045] In some embodiments, the diameter of the conductive substrate is 10μm-200μm, which will not affect the performance of the battery cell and can ensure the mechanical strength of the reference electrode. As an example, it can be 10μm, 25μm, 50μm, 75μm, 100μm, 125μm, 150μm, 175μm, 200μm, etc. or within the range of any two of the above values. The conductive substrate includes any one of metal wire, enameled metal wire, and carbon fiber products. It can be understood that the metal wire can be any existing conductive metal fine wire, including but not limited to copper wire, aluminum wire, platinum wire, and silver wire; the enameled metal wire is an enameled layer coated on the surface of the aforementioned metal wire, and the enameled metal wire in this application can be enameled copper wire, enameled aluminum wire, enameled platinum wire, or enameled silver wire. Carbon fiber products, as the name implies, are various material products made of carbon fiber as raw material, for example, carbon fiber wire.
[0046] According to the second aspect of the present application, there is provided a method for preparing the electrode material according to the first aspect, comprising the following steps:
[0047] S1. Evenly mix the carbon material, aqueous binder and deionized water to prepare a conductive layer slurry with a solid content of 1% to 20%;
[0048] S2, wetting one end of the pretreated conductive substrate with deionized water, and then immersing it in the conductive layer slurry and keeping it for the first time, taking it out, and drying it.
[0049] The conductive layer slurry in the present application is an aqueous heterogeneous system, which is safe, pollution-free, and easy to operate. By utilizing the low dispersibility of carbon materials in deionized water, a conductive layer with high roughness and high adhesion can be formed on the surface of the conductive substrate, thereby increasing the contact area between the electrode material and the sodium metal, increasing the amount of sodium plating, and at the same time enhancing the spatial limiting ability of the powdered sodium metal on the surface of the electrode material, thereby preventing the sodium metal from falling off and causing the sodium-plated reference electrode to fail, improving the stability of the sodium-plated layer, and ensuring the service life of the sodium-plated reference electrode. The applicant has found that the solid content of the conductive layer slurry will have a great influence on the performance of the conductive layer. The conductive layer formed by the slurry with a solid content of 1%-20% can have both high roughness and high adhesion. As an example, the solid content of the conductive layer slurry can be, for example, 1%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5%, 20%, etc. or within the range of any two of the above values. In the present application, the solid content of the conductive layer slurry refers to the proportion of the sum of the mass of the carbon material and the aqueous binder in the total mass of the conductive layer slurry.
[0050] It should be noted that the pretreatment step in S2 includes: when the conductive substrate is a metal wire or an enameled metal wire, placing both ends of the conductive substrate in a dilute acid to remove the oxide or enameled layer to expose the metal; and when the conductive substrate is a carbon fiber product, it only needs to be cleaned with deionized water and / or ethanol. It can be seen that the preparation method of the present application does not need to use concentrated acid to etch the substrate, making the process of the present application simple, time-saving, safe and pollution-free.
[0051] In some embodiments, the first time for the conductive substrate to be immersed in the conductive layer slurry is 5s-30s, thereby ensuring that a conductive layer of sufficient thickness can be formed. As an example, the first time can be 5s, 10s, 15s, 20s, 25s, 30s, etc. or within the range of any two of the above values.
[0052] According to an embodiment of the present application, in a third aspect, a method for preparing a three-electrode sodium ion battery is provided, comprising the following steps:
[0053] S1. Covering the surface of the conductive layer of the electrode material with a separator and placing it in the middle of the battery core; the electrode material is the electrode material described in the first aspect or the electrode material prepared by the preparation method described in the second aspect;
[0054] S2. After the battery cell is packaged, baked, injected, formed, and divided in sequence, a step current sodium plating process is used to deposit a sodium plating layer on the surface of the conductive layer; the step current sodium plating process includes: charging with 1mA-5mA current for 1min-5min, 200μA-1000μA current for 5min-10min, 50μA-200μA current for 10min-30min, and 3μA-50μA current for 30min-240min. Compared with the existing single current sodium plating method, the present application adopts a step current sodium plating process that gradually reduces the charging current and prolongs the charging time, which can significantly reduce the sodium plating time, while also ensuring the uniformity and density of the sodium plating layer.
[0055] It is understandable that in S1, 1-2 layers of diaphragm are coated on the surface of the conductive layer in a winding manner, and the width of the diaphragm is 0.5-2 cm higher than the height of the conductive layer to ensure good insulation. A toothpick is dipped in 0.2%-1% PVDF / NMP solution to bond the tail end of the wound diaphragm. The portion of the electrode material coated with the diaphragm is placed in the geometric middle of the battery cell, and the middle part includes the middle part in the thickness direction of the battery cell, the middle part in the length direction, and the middle part in the width direction. At the same time, the other exposed end of the electrode material (4-8 cm long) is led out of the shell and connected to the reference electrode ear. In S2, the baking, liquid injection, formation, and volume separation processes are completed according to the conventional battery cell manufacturing process. After formation and volume separation, since the negative electrode has been embedded with some sodium ions, and the positive electrode has only been freed from some sodium ions, there is a sodium source in both the positive and negative electrodes, which can provide a sodium source for subsequent sodium plating on the positive electrode side and the negative electrode side. First, the external positive power line is connected to the positive ear of the three-electrode battery cell, and the external negative power line is connected to the reference electrode ear. The sodium plating layer is deposited on the positive side of the electrode material using the above-mentioned step current sodium plating process. Then the external positive power line is connected to the negative ear of the three-electrode battery cell, and the external negative power line is still connected to the reference electrode ear. The sodium plating layer is deposited on the negative side using the same sodium plating method as the positive side, and finally a reference electrode with a uniform and dense sodium plating layer is obtained. It is worth noting that the sodium ion battery reference electrode in this application includes the electrode material and the sodium plating layer arranged at one end of the electrode material.
[0056] by Figure 1-Figure 2 Taking the structure of the three-electrode sodium ion battery of the present application as an example, it can be understood that: Figure 1-Figure 2 The structure shown is only one embodiment of the three-electrode sodium ion battery of the present application and should not be construed as limiting the scope of protection claimed in the present application. Figure 1-Figure 2The three-electrode sodium ion battery of the present application includes an aluminum-plastic film shell 3 and a laminated battery cell arranged inside the aluminum-plastic film shell 3, wherein the laminated battery cell includes a plurality of stacked positive electrode sheets 7, a plurality of negative electrode sheets 8, and a diaphragm 9 arranged between adjacent positive electrode sheets 7 and negative electrode sheets 8, one end of the positive electrode sheet 7 in the width direction is connected to the positive electrode tab 1, and one end of the negative electrode sheet 8 in the width direction is connected to the negative electrode tab 2; the reference electrode includes an enameled metal wire 6 and an effective portion 5 located at one end of the enameled metal wire 6, the effective portion 5 further includes an electrode material and a sodium-plated layer arranged on the surface of the electrode material, the surface of the effective portion 5 is also coated with a diaphragm 9, and the other end of the enameled metal wire 6 is connected to the reference electrode tab 4.
[0057] In some embodiments, the mass ratio of the sodium-plated layer to the electrode material is 1:100-1:40. It can be seen that the sodium content in the sodium-ion battery reference electrode of the present application is 1%-2.5%, which is significantly higher than the sodium content (0.1-0.5%) in the sodium-plated reference electrode prepared by the existing process.
[0058] According to the fourth aspect of the present application, a three-electrode sodium ion battery is also provided, which is prepared by the preparation method described in the third aspect. The three-electrode sodium ion battery of the present application, because it contains a reference electrode with a high sodium content and a uniform, dense and stable sodium plating layer, can perform electrochemical performance testing on the sodium ion battery to accurately monitor the independent potential changes of the positive and negative electrodes during the charging and discharging process of the sodium ion battery.
[0059] The present application is further described in detail below in conjunction with specific examples, and these examples should not be construed as limiting the scope of protection claimed in the present application. Where specific experimental steps or conditions are not specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. Where the manufacturer of the reagents or instruments used is not specified, they are all conventional reagent products that can be obtained commercially.
[0060] Example 1
[0061] This embodiment provides a method for preparing a three-electrode sodium ion battery soft pack including a reference electrode, comprising the following steps:
[0062] 1) A section of enameled copper wire with a length of about 15 cm and a diameter of 50 μm was cut as a substrate, and one end of the enameled copper wire with a length of about 3 cm and the other end of the enameled copper wire with a length of about 5 cm were immersed in dilute hydrochloric acid for 60 min and deionized water for 10 min, and then cleaned and dried to obtain an enameled copper wire with bare ends;
[0063] 2) According to the mass ratio of conductive carbon black to binder SBR of 90%:10%, conductive carbon black (specific surface area of 400m 2 / g) and SBR are added into deionized water and stirred thoroughly to obtain a composite slurry with a solid content of 10%;
[0064] 3) Wetting the 3 cm exposed end of the enameled copper wire pretreated in step 1) with deionized water, and then immersing it in the composite slurry prepared in step 2) so that the 3 cm exposed end of the enameled copper wire is completely covered with the composite slurry, and the immersion time is 15 seconds. After natural drying, an electrode material with one end coated with a conductive layer and an exposed length of 5 cm is obtained, and the thickness of the conductive layer is measured to be about 8 μm, and the surface roughness of the conductive layer is 1.6 μm;
[0065] 4) Cut a diaphragm with a width of about 4 cm, tightly wind the diaphragm on the surface of the conductive layer of the above-mentioned electrode material, and use a toothpick dipped in 0.1% PVDF / NMP solution to adhere the tail end of the wound diaphragm; place the portion of the electrode material coated with the diaphragm in the middle of the battery cell, and at the same time lead the 5 cm exposed end of the electrode material out of the shell and connect it to the reference electrode ear;
[0066] 5) After the three-electrode soft package containing the electrode material is packaged, baked, injected, formed, and divided in sequence, the electrode material is plated with sodium using a step current sodium plating method, and the specific steps are: the external positive power line is connected to the positive ear of the three-electrode battery cell, and the external negative power line is connected to the reference electrode ear, and 2mA current is used for sodium plating for 2min, 500μA for sodium plating for 10min, 100μA for sodium plating for 30min, and 20μA for sodium plating for 60min, so as to deposit a sodium plating layer on the positive electrode side of the electrode material; then the external positive power line is connected to the negative ear of the three-electrode battery cell, and the external negative power line is still connected to the reference electrode ear, and the same sodium plating method as the positive electrode side is used to finally obtain a reference electrode with a uniform and dense sodium plating layer.
[0067] Example 2
[0068] The method is basically the same as Example 1, except that the mass ratio of the conductive carbon black to the SBR in the composite slurry is 80%:20%.
[0069] Example 3
[0070] The method is basically the same as Example 1, except that the mass ratio of conductive carbon black to SBR in the composite slurry is 98%:2%.
[0071] Example 4
[0072] It is basically the same as Example 1, except that the solid content of the composite slurry is 20%.
[0073] Example 5
[0074] It is basically the same as Example 1, except that the solid content of the composite slurry is 1%.
[0075] Example 6
[0076] The same as Example 1, except that the specific surface area is 1000m 2 / g of conductive carbon black.
[0077] Example 7
[0078] The same as Example 1, except that the specific surface area is 200m 2 / g of conductive carbon black.
[0079] Example 8
[0080] The same as Example 1, except that the specific surface area is 60m 2 / g of conductive carbon black.
[0081] Example 9
[0082] It is basically the same as Example 1, except that:
[0083] The enameled aluminum wire with a diameter of 10 μm was selected as the substrate. The mass ratio of Ketjen black to CMC was 85%:15%. Ketjen black (with a specific surface area of 1000 m 2 / g) and CMC were added into deionized water and stirred thoroughly to obtain a composite slurry with a solid content of 15%.
[0084] Example 10
[0085] It is basically the same as Example 1, except that:
[0086] The enameled silver wire with a diameter of 200 μm was selected as the substrate. According to the mass ratio of graphene to PAN of 94%:6%, graphene (with a specific surface area of 300 m 2 / g) and PAN were added into deionized water and stirred thoroughly to obtain a composite slurry with a solid content of 5%.
[0087] Embodiment 11
[0088] The method is the same as Example 1, except that the steps of the step current sodium plating method are: 5 mA for sodium plating for 5 min, 800 μA for sodium plating for 10 min, 200 μA for sodium plating for 30 min and 10 μA for sodium plating for 120 min.
[0089] Example 12
[0090] The method is the same as Example 1, except that the steps of the step current sodium plating method are: sodium plating with 1 mA current for 3 min, sodium plating with 300 μA current for 10 min, sodium plating with 100 μA current for 10 min and sodium plating with 10 μA current for 30 min.
[0091] Comparative Example 1
[0092] It is basically the same as Example 1, except that steps 2) and 3) are omitted.
[0093] Comparative Example 2
[0094] It is basically the same as Example 1, except that the mass ratio of conductive carbon black to SBR in the composite slurry is 78%:22%, and the solid content of the composite slurry is 0.9%.
[0095] Comparative Example 3
[0096] The method is basically the same as Example 1, except that a constant current is used for sodium plating in step 5), that is, a current of 100 μA is used for sodium plating for 102 min.
[0097] Test Case
[0098] 1. Surface roughness test
[0099] The surface roughness of the electrode was tested using a probe-type roughness tester. Ten points were evenly selected along the length of the electrode. After removing the maximum and minimum values, the average value was taken as its surface roughness value.
[0100] 2. Coating thickness test
[0101] The coating thickness is tested using a micrometer with an accuracy of 1 μm. The diameter of the bare end of the enameled copper wire in step 2) of Example 1 is measured, and 10 points are evenly taken along the length direction. After removing the maximum and minimum values, the average value is taken as h1; the diameter of the conductive layer coated in step 3) of Example 1 is obtained by the same method as h2; then the thickness of the conductive coating h0 is: h0=(h2-h1) / 2.
[0102] 3. Specific surface area test
[0103] Refer to GB / T 19587-2004.
[0104] 4. Sodium plating layer quality test
[0105] The quality of the sodium plating layer is obtained by the following calculation method:
[0106] First, the step current sodium plating capacity is:
[0107] Capacity (mAh) = ΣI × t (1)
[0108] Where, I is the step sodium plating current (mA), and t is the sodium plating time corresponding to the step current (h);
[0109] Secondly, according to Faraday's law:
[0110]
[0111] Combining (1) and (2) to obtain the mass of the sodium-plated layer: m(Na) = 0.858 × ∑I × t, unit: mg;
[0112] The sodium content is the ratio of the mass of the sodium plating layer to the sum of the mass of the conductive coating and the bare copper wire bearing the conductive coating, that is: ω=m(Na) / (m(conductive coating)+m(copper wire))*100%.
[0113] 5. Potential test
[0114] The three-electrode cell was charged and discharged using a Biologic multi-channel electrochemical workstation, with a 0.1C rate cycle and a voltage range of 1.5-3.4V to obtain the full-electric, positive electrode vs reference, and negative electrode vs reference potentials. The stability evaluation indicators are:
[0115] If under the same charging system, the difference in the lowest potential of two adjacent charging cycles of the negative electrode is ≤10mV, the electrode potential is stable; if under the same charging system, the lowest charging potential of the negative electrode in the n+1 cycle is greater than that in the n cycle, and the difference is greater than 10mV, then the electrode potential is determined to be unstable; the stable test duration is the test time from the start of the test to the point where the negative electrode potential is unstable.
[0116] The above test results are shown in Table 1-Table 2 and Figure 3-Figure 4 shown.
[0117] Table 1 Structure of sodium-plated reference electrode
[0118] Conductive layer surface roughness (μm) Conductive layer thickness (μm) Sodium plating layer content (%) Example 1 1.6 13 1.18 Example 2 1.4 11 1.15 Example 3 1.9 14 1.20 Example 4 2.3 17 1.24 Example 5 0.7 10 1.10 Example 6 1.8 14 1.20 Example 7 1.7 12 1.18 Example 8 1.2 10 1.12 Example 9 1.6 12 1.23 Example 10 1.5 11 1.15 Embodiment 11 1.6 13 2.50 Example 12 1.6 13 1.12 Comparative Example 1 0.12 / 1.23 Comparative Example 2 0.27 9 1.18 Comparative Example 3 1.6 13 0.70
[0119] Table 2 Potential test results
[0120]
[0121]
[0122] Combining Table 1 and Table 2, it can be seen that compared with Comparative Examples 1-2, the surface roughness of the conductive layer in Examples 1-12 is between 1.1-2.3 μm, which shows that the use of a suitable material ratio can form a high-roughness conductive layer on the surface of the conductive substrate, thereby significantly improving the test stability of the three-electrode battery. The content of the sodium-plated layer in the sodium reference electrode is closely related to the sodium plating process. Compared with Example 1, Comparative Example 3 adopts a constant current sodium plating process, and the sodium-plated layer content obtained is lower, which also affects the test stability of the three-electrode battery. In summary, the conditions for the above-mentioned three-electrode battery to stably detect the potential are: 1) The surface roughness of the conductive layer of the sodium reference electrode in the three-electrode battery must be greater than 0.3 μm; 2) The sodium content of the sodium-plated layer must be greater than or equal to 1%.
[0123] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. An electrode material for a sodium ion battery reference electrode, characterized in that: The electrode material comprises a conductive substrate and a conductive layer coated on one end of the conductive substrate, and the surface roughness of the conductive layer is 0.3 μm-3 μm.
2. The electrode material according to claim 1, characterized in that The surface roughness of the conductive layer is 1.1 μm-2.3 μm; And / or, the thickness of the conductive layer is 1 μm-20 μm; And / or, the conductive layer comprises 80%-98% of the carbon material and 2%-20% of the aqueous binder.
3. The electrode material according to claim 2, characterized in that The specific surface area of the carbon material is 200 m 2 / g-1000m 2 / g; And / or, the thickness of the conductive layer is 10 μm-17 μm.
4. The electrode material according to claim 2 or 3, characterized in that The carbon material includes at least one of conductive carbon black, Ketjen black, carbon nanotubes, and graphene; And / or, the aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, and polyacrylic acid.
5. The electrode material according to claim 1, characterized in that The height of the conductive layer on the conductive substrate accounts for 0.5%-5% of the length of the conductive substrate; And / or, the diameter of the conductive substrate is 10 μm-200 μm; And / or, the conductive substrate includes any one of metal wire, enameled metal wire, and carbon fiber product.
6. The method for preparing the electrode material according to any one of claims 1 to 5, characterized in that: The steps include: S1. Evenly mix the carbon material, aqueous binder and deionized water to prepare a conductive layer slurry with a solid content of 1% to 20%; S2, wetting one end of the pretreated conductive substrate with deionized water, and then immersing it in the conductive layer slurry and keeping it for the first time, taking it out, and drying it.
7. The preparation method according to claim 6, characterized in that: The first time is 5s-30s; And / or, the pretreatment step includes: when the conductive substrate is a metal wire or an enameled metal wire, placing both ends of the conductive substrate in dilute acid to remove oxides or enameling layers; or, when the conductive substrate is a carbon fiber product, cleaning it with deionized water and / or ethanol.
8. A method for preparing a three-electrode sodium ion battery, characterized in that: The steps include: S1. Covering the surface of the conductive layer of the electrode material with a separator and placing it in the middle of the battery cell; the electrode material is the electrode material according to any one of claims 1 to 5 or the electrode material prepared by the preparation method according to any one of claims 6 to 7; S2. After the battery cell is packaged, baked, injected, formed, and divided in sequence, a sodium plating layer is deposited on the surface of the conductive layer using a step current sodium plating process; the step current sodium plating process includes: charging with a current of 1mA-5mA for 1min-5min, a current of 200μA-1000μA for 5min-10min, a current of 50μA-200μA for 10min-30min, and a current of 3μA-50μA for 30min-240min.
9. The method for preparing a three-electrode sodium ion battery according to claim 8, characterized in that: The mass ratio of the sodium plating layer to the electrode material is 1:100-1:
40.
10. A three-electrode sodium ion battery, characterized in that: The preparation method is adopted according to any one of claims 8 to 9.